DESIGN & BUILD A SLURRY TRANSFER CONTROL & MONITORING SYSTEM ON THE ATM 140 SPRAY DRYER USING MICROCONTROLLER WITH ULTRASONIC SENSORS - Adi Winarno; Nur Faizim; Muchammad Lukman Fauszan lukman (BEST, 2022)
In the current developments automation systems have begun to be applied to the industrial world, including the ceramic or tile industry. The ceramic industry in the main raw materials is soil, processing or mixing soil from crusher machines that will be produced into slurry materials ( slurry) using milling time continus (MTC), spray dryer pump machines to distribute slurries from the reservoir center to the ATM 140 reservoir. Often experiences overload slurry on atm 140 reservoirs because the system still uses swith. The operator still turns off the pump manually when there is an overload, based on these problems, an innovation is needed for an innovative slurry transfer control and monitoring tool on the ATM 140 spray dryer using an ultrasonic microcontroller-based sensor and the percentage of the contents of the reservoir that will be displayed on the LCD.